2016
DOI: 10.1152/physiolgenomics.00021.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined progesterone and 17β-estradiol treatment on the transcriptome of cultured human myometrial smooth muscle cells

Abstract: Chandran S, Cairns MT, O'Brien M, O'Connell E, Mashayekhi K, Smith TJ. Effects of combined progesterone and 17␤-estradiol treatment on the transcriptome of cultured human myometrial smooth muscle cells. Physiol Genomics 48: 50 -61, 2016. First published November 3, 2015 doi:10.1152/physiolgenomics.00021.2015.-A transcriptomic analysis of cultured human uterine smooth muscle cells (hUtSMCs) was performed to examine gene expression profiles in smooth muscle in an environment containing the two major steroid horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…One study comparing non-pregnant myometrium at t ¼ 0 to matched primary cell culture reported changes in expression of more than 1000 genes (Zaitseva et al, 2006) supporting our finding of marked changes in gene expression in primary cell culture systems. Some gene expression studies focused on gene expression in myometrial explants (Cordeaux et al, 2010) or cultured myometrial cells (Lei et al, 2015b;Chandran et al, 2016) in the presence or the absence of progestins and hence cannot be compared with our study. Other authors (Rehman et al, 2003;Bollapragada et al, 2009;Mittal et al, 2010;Chan et al, 2014) have sought to compare the gene expression profile of myometrium from non-labouring and labouring patients.…”
Section: Figurementioning
confidence: 99%
“…One study comparing non-pregnant myometrium at t ¼ 0 to matched primary cell culture reported changes in expression of more than 1000 genes (Zaitseva et al, 2006) supporting our finding of marked changes in gene expression in primary cell culture systems. Some gene expression studies focused on gene expression in myometrial explants (Cordeaux et al, 2010) or cultured myometrial cells (Lei et al, 2015b;Chandran et al, 2016) in the presence or the absence of progestins and hence cannot be compared with our study. Other authors (Rehman et al, 2003;Bollapragada et al, 2009;Mittal et al, 2010;Chan et al, 2014) have sought to compare the gene expression profile of myometrium from non-labouring and labouring patients.…”
Section: Figurementioning
confidence: 99%
“…Increasingly, new insights into the molecular biological effects of hormones on leiomyoma cells are being investigated; however, so far no direct therapeutic consequences have emerged. [ 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…4,16 Genetic variants and posttranscriptional regulation alter functional motifs, and alterations in functional motifs may reduce DNA repair capacity and lead to increased cancer risks. 17,18 Our results revealed that miR-4715-3p modulated XPG expression and may have altered its repair ability, resulting in lung cancer [Supplementary Figure 2].…”
Section: Discussionmentioning
confidence: 99%